Ko-infeksi Human Immunodeficiency Virus (HIV) dengan Mycobacterium leprae - Yuni Eka Anggraini (Fakultas Kedokteran Universitas Riau, 2015)
Human immunodefficiency virus (HIV) epidemic covers several countries with endemic leprosy without any significantincrease in the number of patients co-infected with HIV and leprosy, so it can be concluded that HIV-positive does notincrease the risk of developing leprosy. Clinicopathological spectrum of leprosy patients who are co-infected withHIV is not changed. Leprosy may be attributed to the presence of immune recovery syndrome after the administrationof highly active antiretroviral therapy (HAART). Long-term incubation period and the low incidence of leprosy inpatients with HIV make prospective cohort or case-control studies on the prevalence of leprosy among a group of HIVpositive and HIV negative hardly possible to be performed. The benefit of this circumstance is the HIV pandemicdoes not become a nuisance of the effort to control leprosy. Further studies on the molecular pathogenesis of M.leprae and other mycobacterial can provide an understanding of the differences of the pathogenesis in patients withHIV infection.